Self-stochasticity in boundary value problems of quantum mechanics - Krasnyuk, I.B.; Melnik, T.N.; Yurchenko, V.M. (Физика и техника высоких давлений, 2017)
On the example of an initial-value boundary problem for the Schrödinger equation, a methodological problem of quantum mechanics has been discussed. It is shown that quantum mechanical problems can be reduced to difference equations with continuous time for which there exist so-called self-stochastic solutions. Hence, such solutions exist for quantum problems. These solutions are random function as time is large. It is shown that the Sharkovsky metric can be applied for computer simulation of limit distributions of random wave functions.